(untitled) (CIPEEX, 2024)
This work seeks to understand the effects of the civil arrest of the food debtor duringtheCovid-19pandemic,inadditiontotheRevisionalAction,andcoercivemeasuresrelatedto non-compliance with the Food provision. How has the Pandemic caused by Covid-19brought consequences in the legal system in relation to the duty to provide food? What werethe coercive means (civil arrest) like during the pandemic period? Social issues relating tomassiveunemploymentduringthePandemicdirectlyorindirectlyaffectedsuchlegalrelationships. The general objective is to understand and identify how the provision of foodwas handled, as well as the arrestof the food debtor during the pandemic, presenting howthe penalty was applied in the pandemic scenario. Carry out a history of the civil arrestprocedure for the food debtor Identify the legislation applicable to the right to provide food;Clarifythemainaspectsrelatedtothecivilarrestofthefooddebtor;CompareFoodProvision before and after the pandemic. Under Brazilian legislation, civil imprisonment is anextrememeasureapplicableincaseswherethedebtorisindefaultinpayingtheobligationto provide maintenance or when there is a lack of justification regarding the impossibility ofpaying it.The right to alimony has several characteristics. According to specialized doctrine,food law is: very personal; irrevocable; inaccessible; unseizable; imprescriptible; current;incompensable;unrepeatableorirreplaceable;non-transactable;variable;anddivisible.Originally,inourcountry,prisonsforfooddebtorsarenecessarilyclosed.However,inviewof the changes that the Covid-19 pandemic brought to the world, it was up to the judiciary toreinvent itself in the way of dealing with its matters, and one of these changes was the way ofdealing with food defaulters, which had its prison converted from closed to home regime(MOURA; SILVA, 2020). The methodology that will be used in the work is literature review.For Brizola et al (2017), the Literature Review or IR is nothing more than the meeting, thejoining of ideas from different authors on a given topic, achieved through readings andresearchcarriedoutbytheresearcher.Theliteraturereviewis,inthissense,thedocumentation made by the researcher about the work, the research that he or she isproposing to carry out. It is worth highlighting that the work being done will not be somethingtotally original, especially because the literature review is a critical compilation of works thatdiscuss a theme, that is, the literature review, as it is a dialogue carried out between theresearcher-writer of the work and the authors chosen by him to debate the topic, results in atext that does not need to be unpublished, but rather an analytical and critical text oftheideasstudiedonthetopicchosenforthework.